De novo TRIM8 variants impair its protein localization to nuclear bodies and cause developmental delay, epilepsy, and focal segmental glomerulosclerosis. - Weng, Patricia L; Majmundar, Amar J; Khan, Kamal; Lim, Tze Y; Shril, Shirlee; Jin, Gina; Musgrove, John; Wang, Minxian; Ahram, Dina F; Aggarwal, Vimla S; Bier, Louise E; Heinzen, Erin L; et al. (Am J Hum Genet, 2021)
Focal segmental glomerulosclerosis (FSGS) is the main pathology underlying steroid-resistant nephrotic syndrome (SRNS) and a leading cause of chronic kidney disease. Monogenic forms of pediatric SRNS are predominantly caused by recessive mutations, while the contribution of de novo variants (DNVs) to this trait is poorly understood. Using exome sequencing (ES) in a proband with FSGS/SRNS, developmental delay, and epilepsy, we discovered a nonsense DNV in TRIM8, which encodes the E3 ubiquitin ligase tripartite motif containing 8. To establish whether TRIM8 variants represent a cause of FSGS, we aggregated exome/genome-sequencing data for 2,501 pediatric FSGS/SRNS-affected individuals and 48,556 control subjects, detecting eight heterozygous TRIM8 truncating variants in affected subjects but none in control subjects (p = 3.28 × 10). In all six cases with available parental DNA, we demonstrated de novo inheritance (p = 2.21 × 10). Reverse phenotyping revealed neurodevelopmental disease in all eight families. We next analyzed ES from 9,067 individuals with epilepsy, yielding three additional families with truncating TRIM8 variants. Clinical review revealed FSGS in all. All TRIM8 variants cause protein truncation clustering within the last exon between residues 390 and 487 of the 551 amino acid protein, indicating a correlation between this syndrome and loss of the TRIM8 C-terminal region. Wild-type TRIM8 overexpressed in immortalized human podocytes and neuronal cells localized to nuclear bodies, while constructs harboring patient-specific variants mislocalized diffusely to the nucleoplasm. Co-localization studies demonstrated that Gemini and Cajal bodies frequently abut a TRIM8 nuclear body. Truncating TRIM8 DNVs cause a neuro-renal syndrome via aberrant TRIM8 localization, implicating nuclear bodies in FSGS and developmental brain disease.
Keywords: Adult; Animals; Carrier Proteins; Cell Line; Child; Child, Preschool; Codon, Nonsense; Developmental Disabilities; Epilepsy; Female; Glomerulosclerosis, Focal Segmental; Humans; Intranuclear Space; Kidney; Male; Mice; Mutation; Nephrotic Syndrome; Nerve Tissue Proteins; Phenotype; Podocytes; Whole Exome Sequencing

Generation of Monogenic Candidate Genes for Human Nephrotic Syndrome Using 3 Independent Approaches. - Klämbt, Verena; Mao, Youying; Schneider, Ronen; Buerger, Florian; Shamseldin, Hanan; Onuchic-Whitford, Ana C; Deutsch, Konstantin; Kitzler, Thomas M; Nakayama, Makiko; Majmundar, Amar J; Mann, Nina; Hugo, Hannah; et al. (Kidney Int Rep, 2021)
Introduction: Steroid-resistant nephrotic syndrome (SRNS) is the second most common cause of chronic kidney disease during childhood. Identification of 63 monogenic human genes has delineated 12 distinct pathogenic pathways. Methods: Here, we generated 2 independent sets of nephrotic syndrome (NS) candidate genes to augment the discovery of additional monogenic causes based on whole-exome sequencing (WES) data from 1382 families with NS. Results: We first identified 63 known monogenic causes of NS in mice from public databases and scientific publications, and 12 of these genes overlapped with the 63 known human monogenic SRNS genes. Second, we used a set of 64 genes that are regulated by the transcription factor Wilms tumor 1 (WT1), which causes SRNS if mutated. Thirteen of these WT1-regulated genes overlapped with human or murine NS genes. Finally, we overlapped these lists of murine and WT1 candidate genes with our list of 120 candidate genes generated from WES in 1382 NS families, to identify novel candidate genes for monogenic human SRNS. Using this approach, we identified 7 overlapping genes, of which 3 genes were shared by all datasets, including . We show that loss-of-function of leads to decreased CDC42 activity and reduced podocyte migration rate, both of which are rescued by overexpression of wild-type complementary DNA (cDNA), but not by cDNA representing the patient mutation. Conclusion: Thus, we identified 3 novel candidate genes for human SRNS using 3 independent, nonoverlapping hypotheses, and generated functional evidence for as a novel potential monogenic cause of NS.

Mutations in transcription factor CP2-like 1 may cause a novel syndrome with distal renal tubulopathy in humans. - Klämbt, Verena; Werth, Max; Onuchic-Whitford, Ana C; Getwan, Maike; Kitzler, Thomas M; Buerger, Florian; Mao, Youying; Deutsch, Konstantin; Mann, Nina; Majmundar, Amar J; Kaminski, Michael M; Shen, Tian; et al. (Nephrol Dial Transplant, 2021)
BACKGROUND: An underlying monogenic cause of early-onset chronic kidney disease (CKD) can be detected in ∼20% of individuals. For many etiologies of CKD manifesting before 25 years of age, >200 monogenic causative genes have been identified to date, leading to the elucidation of mechanisms of renal pathogenesis. METHODS: In 51 families with echogenic kidneys and CKD, we performed whole-exome sequencing to identify novel monogenic causes of CKD. RESULTS: We discovered a homozygous truncating mutation in the transcription factor gene transcription factor CP2-like 1 (TFCP2L1) in an Arabic patient of consanguineous descent. The patient developed CKD by the age of 2 months and had episodes of severe hypochloremic, hyponatremic and hypokalemic alkalosis, seizures, developmental delay and hypotonia together with cataracts. We found that TFCP2L1 was localized throughout kidney development particularly in the distal nephron. Interestingly, TFCP2L1 induced the growth and development of renal tubules from rat mesenchymal cells. Conversely, the deletion of TFCP2L1 in mice was previously shown to lead to reduced expression of renal cell markers including ion transporters and cell identity proteins expressed in different segments of the distal nephron. TFCP2L1 localized to the nucleus in HEK293T cells only upon coexpression with its paralog upstream-binding protein 1 (UBP1). A TFCP2L1 mutant complementary DNA (cDNA) clone that represented the patient's mutation failed to form homo- and heterodimers with UBP1, an essential step for its transcriptional activity. CONCLUSION: Here, we identified a loss-of-function TFCP2L1 mutation as a potential novel cause of CKD in childhood accompanied by a salt-losing tubulopathy.
Keywords: Animals; Child; DNA-Binding Proteins; Epithelial-Mesenchymal Transition; Female; HEK293 Cells; Humans; Kidney Diseases; Mice; Mice, Knockout; Mutation; Rats; Repressor Proteins; Single-Cell Analysis; Transcription Factors; Whole Exome Sequencing

DAAM2 Variants Cause Nephrotic Syndrome via Actin Dysregulation. - Schneider, Ronen; Deutsch, Konstantin; Hoeprich, Gregory J; Marquez, Jonathan; Hermle, Tobias; Braun, Daniela A; Seltzsam, Steve; Kitzler, Thomas M; Mao, Youying; Buerger, Florian; Majmundar, Amar J; Onuchic-Whitford, Ana C; et al. (Am J Hum Genet, 2020)
The discovery of >60 monogenic causes of nephrotic syndrome (NS) has revealed a central role for the actin regulators RhoA/Rac1/Cdc42 and their effectors, including the formin INF2. By whole-exome sequencing (WES), we here discovered bi-allelic variants in the formin DAAM2 in four unrelated families with steroid-resistant NS. We show that DAAM2 localizes to the cytoplasm in podocytes and in kidney sections. Further, the variants impair DAAM2-dependent actin remodeling processes: wild-type DAAM2 cDNA, but not cDNA representing missense variants found in individuals with NS, rescued reduced podocyte migration rate (PMR) and restored reduced filopodia formation in shRNA-induced DAAM2-knockdown podocytes. Filopodia restoration was also induced by the formin-activating molecule IMM-01. DAAM2 also co-localizes and co-immunoprecipitates with INF2, which is intriguing since variants in both formins cause NS. Using in vitro bulk and TIRF microscopy assays, we find that DAAM2 variants alter actin assembly activities of the formin. In a Xenopus daam2-CRISPR knockout model, we demonstrate actin dysregulation in vivo and glomerular maldevelopment that is rescued by WT-DAAM2 mRNA. We conclude that DAAM2 variants are a likely cause of monogenic human SRNS due to actin dysregulation in podocytes. Further, we provide evidence that DAAM2-associated SRNS may be amenable to treatment using actin regulating compounds.
Keywords: Actins; Alleles; Animals; Animals, Genetically Modified; Cell Movement; Cytoplasm; Formins; Genetic Variation; Humans; Kidney; Kidney Glomerulus; Microfilament Proteins; Mutation, Missense; Nephrotic Syndrome; Podocytes; Pseudopodia; rho GTP-Binding Proteins; RNA, Small Interfering; Whole Exome Sequencing; Xenopus

Mutations of the Transcriptional Corepressor ZMYM2 Cause Syndromic Urinary Tract Malformations. - Connaughton, Dervla M; Dai, Rufeng; Owen, Danielle J; Marquez, Jonathan; Mann, Nina; GrAHm-Paquin, Adda L; Nakayama, Makiko; Coyaud, Etienne; Laurent, Estelle M N; St-Germain, Jonathan R; Blok, Lot Snijders; Vino, Arianna; et al. (Am J Hum Genet, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUT) constitute one of the most frequent birth defects and represent the most common cause of chronic kidney disease in the first three decades of life. Despite the discovery of dozens of monogenic causes of CAKUT, most pathogenic pathways remain elusive. We performed whole-exome sequencing (WES) in 551 individuals with CAKUT and identified a heterozygous de novo stop-gain variant in ZMYM2 in two different families with CAKUT. Through collaboration, we identified in total 14 different heterozygous loss-of-function mutations in ZMYM2 in 15 unrelated families. Most mutations occurred de novo, indicating possible interference with reproductive function. Human disease features are replicated in X. tropicalis larvae with morpholino knockdowns, in which expression of truncated ZMYM2 proteins, based on individual mutations, failed to rescue renal and craniofacial defects. Moreover, heterozygous Zmym2-deficient mice recapitulated features of CAKUT with high penetrance. The ZMYM2 protein is a component of a transcriptional corepressor complex recently linked to the silencing of developmentally regulated endogenous retrovirus elements. Using protein-protein interaction assays, we show that ZMYM2 interacts with additional epigenetic silencing complexes, as well as confirming that it binds to FOXP1, a transcription factor that has also been linked to CAKUT. In summary, our findings establish that loss-of-function mutations of ZMYM2, and potentially that of other proteins in its interactome, as causes of human CAKUT, offering new routes for studying the pathogenesis of the disorder.
Keywords: Amphibian Proteins; Animals; Case-Control Studies; Child; Child, Preschool; DNA-Binding Proteins; Epigenesis, Genetic; Family; Female; Forkhead Transcription Factors; Heterozygote; Humans; Infant; Larva; Male; Mice; Mice, Knockout; Morpholinos; Mutation; Pedigree; Protein Binding; Repressor Proteins; Transcription Factors; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing; Xenopus

Phenotype expansion of heterozygous FOXC1 pathogenic variants toward involvement of congenital anomalies of the kidneys and urinary tract (CAKUT). - Wu, Chen-Han Wilfred; Mann, Nina; Nakayama, Makiko; Connaughton, Dervla M; Dai, Rufeng; Kolvenbach, Caroline M; Kause, Franziska; Ottlewski, Isabel; Wang, Chunyan; Klämbt, Verena; Seltzsam, Steve; Lai, Ethan W; et al. (Genet Med, 2020)
PURPOSE: Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of chronic kidney disease in childhood and adolescence. We aim to identify novel monogenic causes of CAKUT. METHODS: Exome sequencing was performed in 550 CAKUT-affected families. RESULTS: We discovered seven FOXC1 heterozygous likely pathogenic variants within eight CAKUT families. These variants are either never reported, or present in <5 alleles in the gnomAD database with ~141,456 controls. FOXC1 is a causal gene for Axenfeld-Rieger syndrome type 3 and anterior segment dysgenesis 3. Pathogenic variants in FOXC1 have not been detected in patients with CAKUT yet. Interestingly, mouse models for Foxc1 show severe CAKUT phenotypes with incomplete penetrance and variable expressivity. The FOXC1 variants are enriched in the CAKUT cohort compared with the control. Genotype-phenotype correlations showed that Axenfeld-Rieger syndrome or anterior segment dysgenesis can be caused by both truncating and missense pathogenic variants, and the missense variants are located at the forkhead domain. In contrast, for CAKUT, there is no truncating pathogenic variant, and all variants except one are located outside the forkhead domain. CONCLUSION: We thereby expanded the phenotype of FOXC1 pathogenic variants toward involvement of CAKUT, which can potentially be explained by allelism.
Keywords: Child; Eye Abnormalities; Forkhead Transcription Factors; Heterozygote; Humans; Kidney; Phenotype; Urinary Tract

Whole exome sequencing identified ATP6V1C2 as a novel candidate gene for recessive distal renal tubular acidosis. - Jobst-Schwan, Tilman; Klämbt, Verena; Tarsio, Maureen; Heneghan, John F; Majmundar, Amar J; Shril, Shirlee; Buerger, Florian; Ottlewski, Isabel; Shmukler, Boris E; Topaloglu, Rezan; Hashmi, Seema; Hafeez, Farkhanda; et al. (Kidney Int, 2020)
Distal renal tubular acidosis is a rare renal tubular disorder characterized by hyperchloremic metabolic acidosis and impaired urinary acidification. Mutations in three genes (ATP6V0A4, ATP6V1B1 and SLC4A1) constitute a monogenic causation in 58-70% of familial cases of distal renal tubular acidosis. Recently, mutations in FOXI1 have been identified as an additional cause. Therefore, we hypothesized that further monogenic causes of distal renal tubular acidosis remain to be discovered. Panel sequencing and/or whole exome sequencing was performed in a cohort of 17 families with 19 affected individuals with pediatric onset distal renal tubular acidosis. A causative mutation was detected in one of the three "classical" known distal renal tubular acidosis genes in 10 of 17 families. The seven unsolved families were then subjected to candidate whole exome sequencing analysis. Potential disease causing mutations in three genes were detected: ATP6V1C2, which encodes another kidney specific subunit of the V-type proton ATPase (1 family); WDR72 (2 families), previously implicated in V-ATPase trafficking in cells; and SLC4A2 (1 family), a paralog of the known distal renal tubular acidosis gene SLC4A1. Two of these mutations were assessed for deleteriousness through functional studies. Yeast growth assays for ATP6V1C2 revealed loss-of-function for the patient mutation, strongly supporting ATP6V1C2 as a novel distal renal tubular acidosis gene. Thus, we provided a molecular diagnosis in a known distal renal tubular acidosis gene in 10 of 17 families (59%) with this disease, identified mutations in ATP6V1C2 as a novel human candidate gene, and provided further evidence for phenotypic expansion in WDR72 mutations from amelogenesis imperfecta to distal renal tubular acidosis.

COL4A1 mutations as a potential novel cause of autosomal dominant CAKUT in humans. - Kitzler, Thomas M; Schneider, Ronen; Kohl, Stefan; Kolvenbach, Caroline M; Connaughton, Dervla M; Dai, Rufeng; Mann, Nina; Nakayama, Makiko; Majmundar, Amar J; Wu, Chen-Han W; Kari, Jameela A; El Desoky, Sherif M; et al. (Hum Genet, 2019)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of chronic kidney disease (~ 45%) that manifests before 30 years of age. The genetic locus containing COL4A1 (13q33-34) has been implicated in vesicoureteral reflux (VUR), but mutations in COL4A1 have not been reported in CAKUT. We hypothesized that COL4A1 mutations cause CAKUT in humans. We performed whole exome sequencing (WES) in 550 families with CAKUT. As negative control cohorts we used WES sequencing data from patients with nephronophthisis (NPHP) with no genetic cause identified (n = 257) and with nephrotic syndrome (NS) due to monogenic causes (n = 100). We identified a not previously reported heterozygous missense variant in COL4A1 in three siblings with isolated VUR. When examining 549 families with CAKUT, we identified nine additional different heterozygous missense mutations in COL4A1 in 11 individuals from 11 unrelated families with CAKUT, while no COL4A1 mutations were identified in a control cohort with NPHP and only one in the cohort with NS. Most individuals (12/14) had isolated CAKUT with no extrarenal features. The predominant phenotype was VUR (9/14). There were no clinical features of the COL4A1-related disorders (e.g., HANAC syndrome, porencephaly, tortuosity of retinal arteries). Whereas COL4A1-related disorders are typically caused by glycine substitutions in the collagenous domain (84.4% of variants), only one variant in our cohort is a glycine substitution within the collagenous domain (1/10). We identified heterozygous COL4A1 mutations as a potential novel autosomal dominant cause of CAKUT that is allelic to the established COL4A1-related disorders and predominantly caused by non-glycine substitutions.
Keywords: Alleles; Amino Acid Substitution; Collagen Type IV; Computational Biology; Congenital Abnormalities; Databases, Genetic; DNA Mutational Analysis; Evolution, Molecular; Female; Genetic Association Studies; Genetic Loci; Genomics; Heterozygote; Humans; Kidney; Kidney Diseases, Cystic; Male; Mutation; Nephrotic Syndrome; Phenotype; Urinary Tract; Web Browser; Whole Exome Sequencing

Dominant PAX2 mutations may cause steroid-resistant nephrotic syndrome and FSGS in children. - Vivante, Asaf; Chacham, Orna Staretz; Shril, Shirlee; Schreiber, Ruth; Mane, Shrikant M; Pode-Shakked, Ben; Soliman, Neveen A; Koneth, Irene; Schiffer, Mario; Anikster, Yair; Hildebrandt, Friedhelm (Pediatr Nephrol, 2019)
BACKGROUND: Heterozygous PAX2 mutations cause renal coloboma syndrome (RCS) [OMIM no. 120330]. RCS is a renal syndromic disease encompassing retinal coloboma and sensorineural hearing loss. Recently, a causative role for PAX2 was reported in adult-onset nephrotic syndrome secondary to focal segmental glomerulosclerosis (FSGS). However, the prevalence of PAX2 mutations among large cohort of children with steroid-resistant nephrotic syndrome (SRNS) and FSGS has not been systematically studied. METHODS: We employed whole-exome sequencing (WES) to identify the percentage of SRNS cases explained by monogenic mutations in known genes of SRNS/FSGS. As PAX2 mutations are not an established cause of childhood FSGS, we evaluated a cohort of 215 unrelated families with SRNS, in whom no underlying genetic etiology had been previously established. RESULTS: Using WES, we identified 3 novel causative heterozygous PAX2 mutations in 3 out of the 215 unrelated index cases studied (1.3%). All three cases were detected in individuals from families with more than one affected and compatible with an autosomal dominant mode of inheritance (3/57 familial cases studied (5.2%)). The clinical diagnosis in three out of four pediatric index patients was done during routine medical evaluation. CONCLUSIONS: Our findings demonstrate high frequency of PAX2 mutations in familial form of SRNS (5.2%) and further expand the phenotypic spectrum of PAX2 heterozygous mutations to include autosomal dominant childhood-onset FSGS. These results highlight the importance of including PAX2 in the list of genes known to cause FSGS in children.

Genetic variants in the LAMA5 gene in pediatric nephrotic syndrome. - Braun, Daniela A; Warejko, Jillian K; Ashraf, Shazia; Tan, Weizhen; Daga, Ankana; Schneider, Ronen; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; Majmundar, Amar J; Nakayama, Makiko; Schapiro, David; et al. (Nephrol Dial Transplant, 2019)
BACKGROUND: Nephrotic syndrome (NS), a chronic kidney disease, is characterized by significant loss of protein in the urine causing hypoalbuminemia and edema. In general, ∼15% of childhood-onset cases do not respond to steroid therapy and are classified as steroid-resistant NS (SRNS). In ∼30% of cases with SRNS, a causative mutation can be detected in one of 44 monogenic SRNS genes. The gene LAMA5 encodes laminin-α5, an essential component of the glomerular basement membrane. Mice with a hypomorphic mutation in the orthologous gene Lama5 develop proteinuria and hematuria. METHODS: To identify additional monogenic causes of NS, we performed whole exome sequencing in 300 families with pediatric NS. In consanguineous families we applied homozygosity mapping to identify genomic candidate loci for the underlying recessive mutation. RESULTS: In three families, in whom mutations in known NS genes were excluded, but in whom a recessive, monogenic cause of NS was strongly suspected based on pedigree information, we identified homozygous variants of unknown significance (VUS) in the gene LAMA5. While all affected individuals had nonsyndromic NS with an early onset of disease, their clinical outcome and response to immunosuppressive therapy differed notably. CONCLUSION: We here identify recessive VUS in the gene LAMA5 in patients with partially treatment-responsive NS. More data will be needed to determine the impact of these VUS in disease management. However, familial occurrence of disease, data from genetic mapping and a mouse model that recapitulates the NS phenotypes suggest that these genetic variants may be inherited factors that contribute to the development of NS in pediatric patients.

Monogenic causes of chronic kidney disease in adults. - Connaughton, Dervla M; Kennedy, Claire; Shril, Shirlee; Mann, Nina; Murray, Susan L; Williams, Patrick A; Conlon, Eoin; Nakayama, Makiko; van der Ven, Amelie T; Ityel, Hadas; Kause, Franziska; Kolvenbach, Caroline M; et al. (Kidney Int, 2019)
Approximately 500 monogenic causes of chronic kidney disease (CKD) have been identified, mainly in pediatric populations. The frequency of monogenic causes among adults with CKD has been less extensively studied. To determine the likelihood of detecting monogenic causes of CKD in adults presenting to nephrology services in Ireland, we conducted whole exome sequencing (WES) in a multi-centre cohort of 114 families including 138 affected individuals with CKD. Affected adults were recruited from 78 families with a positive family history, 16 families with extra-renal features, and 20 families with neither a family history nor extra-renal features. We detected a pathogenic mutation in a known CKD gene in 42 of 114 families (37%). A monogenic cause was identified in 36% of affected families with a positive family history of CKD, 69% of those with extra-renal features, and only 15% of those without a family history or extra-renal features. There was no difference in the rate of genetic diagnosis in individuals with childhood versus adult onset CKD. Among the 42 families in whom a monogenic cause was identified, WES confirmed the clinical diagnosis in 17 (40%), corrected the clinical diagnosis in 9 (22%), and established a diagnosis for the first time in 16 families referred with CKD of unknown etiology (38%). In this multi-centre study of adults with CKD, a molecular genetic diagnosis was established in over one-third of families. In the evolving era of precision medicine, WES may be an important tool to identify the cause of CKD in adults.

Mutations in KIRREL1, a slit diaphragm component, cause steroid-resistant nephrotic syndrome. - Solanki, Ashish K; Widmeier, Eugen; Arif, Ehtesham; Sharma, Shailza; Daga, Ankana; Srivastava, Pankaj; Kwon, Sang-Ho; Hugo, Hannah; Nakayama, Makiko; Mann, Nina; Majmundar, Amar J; Tan, Wei; et al. (Kidney Int, 2019)
Steroid-resistant nephrotic syndrome is a frequent cause of chronic kidney disease almost inevitably progressing to end-stage renal disease. More than 58 monogenic causes of SRNS have been discovered and majority of known steroid-resistant nephrotic syndrome causing genes are predominantly expressed in glomerular podocytes, placing them at the center of disease pathogenesis. Herein, we describe two unrelated families with steroid-resistant nephrotic syndrome with homozygous mutations in the KIRREL1 gene. One mutation showed high frequency in the European population (minor allele frequency 0.0011) and this patient achieved complete remission following treatment, but later progressed to chronic kidney disease. We found that mutant KIRREL1 proteins failed to localize to the podocyte cell membrane, indicating defective trafficking and impaired podocytes function. Thus, the KIRREL1 gene product has an important role in modulating the integrity of the slit diaphragm and maintaining glomerular filtration function.

Whole-Exome Sequencing Enables a Precision Medicine Approach for Kidney Transplant Recipients. - Mann, Nina; Braun, Daniela A; Amann, Kassaundra; Tan, Weizhen; Shril, Shirlee; Connaughton, Dervla M; Nakayama, Makiko; Schneider, Ronen; Kitzler, Thomas M; van der Ven, Amelie T; Chen, Jing; Ityel, Hadas; et al. (J Am Soc Nephrol, 2019)
BACKGROUND: Whole-exome sequencing (WES) finds a CKD-related mutation in approximately 20% of patients presenting with CKD before 25 years of age. Although provision of a molecular diagnosis could have important implications for clinical management, evidence is lacking on the diagnostic yield and clinical utility of WES for pediatric renal transplant recipients. METHODS: To determine the diagnostic yield of WES in pediatric kidney transplant recipients, we recruited 104 patients who had received a transplant at Boston Children's Hospital from 2007 through 2017, performed WES, and analyzed results for likely deleterious variants in approximately 400 genes known to cause CKD. RESULTS: By WES, we identified a genetic cause of CKD in 34 out of 104 (32.7%) transplant recipients. The likelihood of detecting a molecular genetic diagnosis was highest for patients with urinary stone disease (three out of three individuals), followed by renal cystic ciliopathies (seven out of nine individuals), steroid-resistant nephrotic syndrome (nine out of 21 individuals), congenital anomalies of the kidney and urinary tract (ten out of 55 individuals), and chronic glomerulonephritis (one out of seven individuals). WES also yielded a molecular diagnosis for four out of nine individuals with ESRD of unknown etiology. The WES-related molecular genetic diagnosis had implications for clinical care for five patients. CONCLUSIONS: Nearly one third of pediatric renal transplant recipients had a genetic cause of their kidney disease identified by WES. Knowledge of this genetic information can help guide management of both transplant patients and potential living related donors.
Keywords: Adolescent; Boston; Child; Child, Preschool; Cohort Studies; Female; Genetic Predisposition to Disease; Genetic Testing; Graft Rejection; Graft Survival; Hospitals, Pediatric; Humans; Kidney Transplantation; Male; Precision Medicine; Prognosis; Renal Insufficiency, Chronic; Retrospective Studies; Risk Assessment; Severity of Illness Index; Survival Analysis; Transplant Recipients; Treatment Outcome; Whole Exome Sequencing

and Mutations Implicate RAB5 Regulation in Nephrotic Syndrome. - Hermle, Tobias; Schneider, Ronen; Schapiro, David; Braun, Daniela A; van der Ven, Amelie T; Warejko, Jillian K; Daga, Ankana; Widmeier, Eugen; Nakayama, Makiko; Jobst-Schwan, Tilman; Majmundar, Amar J; Ashraf, Shazia; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Steroid-resistant nephrotic syndrome (SRNS) is a frequent cause of CKD. The discovery of monogenic causes of SRNS has revealed specific pathogenetic pathways, but these monogenic causes do not explain all cases of SRNS. METHODS: To identify novel monogenic causes of SRNS, we screened 665 patients by whole-exome sequencing. We then evaluated the functional significance of two genes and the mutations therein that we discovered through this sequencing and conducted complementary studies in podocyte-like nephrocytes. RESULTS: We identified conserved, homozygous missense mutations of in two families with early-onset NS and a homozygous missense mutation of in two siblings with SRNS. GAPVD1 and ANKFY1 interact with the endosomal regulator RAB5. Coimmunoprecipitation assays indicated interaction between GAPVD1 and ANKFY1 proteins, which also colocalized when expressed in HEK293T cells. Silencing either protein diminished the podocyte migration rate. Compared with wild-type GAPVD1 and ANKFY1, the mutated proteins produced upon ectopic expression of or bearing the patient-derived mutations exhibited altered binding affinity for active RAB5 and reduced ability to rescue the knockout-induced defect in podocyte migration. Coimmunoprecipitation assays further demonstrated a physical interaction between nephrin and GAPVD1, and immunofluorescence revealed partial colocalization of these proteins in rat glomeruli. The patient-derived mutations reduced nephrin-GAPVD1 binding affinity. In , silencing impaired endocytosis and caused mistrafficking of the nephrin ortholog. CONCLUSIONS: Mutations in and probably in are novel monogenic causes of NS. The discovery of these genes implicates RAB5 regulation in the pathogenesis of human NS.

A homozygous missense variant in VWA2, encoding an interactor of the Fraser-complex, in a patient with vesicoureteral reflux. - van der Ven, Amelie T; Kobbe, Birgit; Kohl, Stefan; Shril, Shirlee; Pogoda, Hans-Martin; Imhof, Thomas; Ityel, Hadas; Vivante, Asaf; Chen, Jing; Hwang, Daw-Yang; Connaughton, Dervla M; Mann, Nina; et al. (PLoS One, 2018)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause (40-50%) of chronic kidney disease (CKD) in children. About 40 monogenic causes of CAKUT have so far been discovered. To date less than 20% of CAKUT cases can be explained by mutations in these 40 genes. To identify additional monogenic causes of CAKUT, we performed whole exome sequencing (WES) and homozygosity mapping (HM) in a patient with CAKUT from Indian origin and consanguineous descent. We identified a homozygous missense mutation (c.1336C>T, p.Arg446Cys) in the gene Von Willebrand factor A domain containing 2 (VWA2). With immunohistochemistry studies on kidneys of newborn (P1) mice, we show that Vwa2 and Fraser extracellular matrix complex subunit 1 (Fras1) co-localize in the nephrogenic zone of the renal cortex. We identified a pronounced expression of Vwa2 in the basement membrane of the ureteric bud (UB) and derivatives of the metanephric mesenchyme (MM). By applying in vitro assays, we demonstrate that the Arg446Cys mutation decreases translocation of monomeric VWA2 protein and increases translocation of aggregated VWA2 protein into the extracellular space. This is potentially due to the additional, unpaired cysteine residue in the mutated protein that is used for intermolecular disulfide bond formation. VWA2 is a known, direct interactor of FRAS1 of the Fraser-Complex (FC). FC-encoding genes and interacting proteins have previously been implicated in the pathogenesis of syndromic and/or isolated CAKUT phenotypes in humans. VWA2 therefore constitutes a very strong candidate in the search for novel CAKUT-causing genes. Our results from in vitro experiments indicate a dose-dependent neomorphic effect of the Arg446Cys homozygous mutation in VWA2.
Keywords: Amino Acid Sequence; Amino Acid Substitution; Animals; Animals, Newborn; Biomarkers, Tumor; Child; Consanguinity; Conserved Sequence; Exons; Extracellular Matrix Proteins; Fraser Syndrome; Gene Expression Regulation, Developmental; Homozygote; Humans; Male; Mice; Models, Animal; Models, Molecular; Mutation, Missense; Pedigree; Sequence Homology, Amino Acid; Urogenital Abnormalities; Urogenital System; Vesico-Ureteral Reflux

Mutations in multiple components of the nuclear pore complex cause nephrotic syndrome. - Braun, Daniela A; Lovric, Svjetlana; Schapiro, David; Schneider, Ronen; Marquez, Jonathan; Asif, Maria; Hussain, Muhammad Sajid; Daga, Ankana; Widmeier, Eugen; Rao, Jia; Ashraf, Shazia; Tan, Weizhen; et al. (J Clin Invest, 2018)
Steroid-resistant nephrotic syndrome (SRNS) almost invariably progresses to end-stage renal disease. Although more than 50 monogenic causes of SRNS have been described, a large proportion of SRNS remains unexplained. Recently, it was discovered that mutations of NUP93 and NUP205, encoding 2 proteins of the inner ring subunit of the nuclear pore complex (NPC), cause SRNS. Here, we describe mutations in genes encoding 4 components of the outer rings of the NPC, namely NUP107, NUP85, NUP133, and NUP160, in 13 families with SRNS. Using coimmunoprecipitation experiments, we showed that certain pathogenic alleles weakened the interaction between neighboring NPC subunits. We demonstrated that morpholino knockdown of nup107, nup85, or nup133 in Xenopus disrupted glomerulogenesis. Re-expression of WT mRNA, but not of mRNA reflecting mutations from SRNS patients, mitigated this phenotype. We furthermore found that CRISPR/Cas9 knockout of NUP107, NUP85, or NUP133 in podocytes activated Cdc42, an important effector of SRNS pathogenesis. CRISPR/Cas9 knockout of nup107 or nup85 in zebrafish caused developmental anomalies and early lethality. In contrast, an in-frame mutation of nup107 did not affect survival, thus mimicking the allelic effects seen in humans. In conclusion, we discovered here that mutations in 4 genes encoding components of the outer ring subunits of the NPC cause SRNS and thereby provide further evidence that specific hypomorphic mutations in these essential genes cause a distinct, organ-specific phenotype.

Mutations in WDR4 as a new cause of Galloway-Mowat syndrome. - Braun, Daniela A; Shril, Shirlee; Sinha, Aditi; Schneider, Ronen; Tan, Weizhen; Ashraf, Shazia; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; Majmundar, Amar J; Daga, Ankana; Warejko, Jillian K; et al. (Am J Med Genet A, 2018)
Galloway-Mowat syndrome (GAMOS) is a phenotypically heterogeneous disorder characterized by neurodevelopmental defects combined with renal-glomerular disease, manifesting with proteinuria. To identify additional monogenic disease causes, we here performed whole exome sequencing (WES), linkage analysis, and homozygosity mapping in three affected siblings of an Indian family with GAMOS. Applying established criteria for variant filtering, we identify a novel homozygous splice site mutation in the gene WDR4 as the likely disease-causing mutation in this family. In line with previous reports, we observe growth deficiency, microcephaly, developmental delay, and intellectual disability as phenotypic features resulting from WDR4 mutations. However, the newly identified allele additionally gives rise to proteinuria and nephrotic syndrome, a phenotype that was never reported in patients with WDR4 mutations. Our data thus expand the phenotypic spectrum of WDR4 mutations by demonstrating that, depending on the specific mutated allele, a renal phenotype may be present. This finding suggests that GAMOS may occupy a phenotypic spectrum with other microcephalic diseases. Furthermore, WDR4 is an additional example of a gene that encodes a tRNA modifying enzyme and gives rise to GAMOS, if mutated. Our findings thereby support the recent observation that, like neurons, podocytes of the renal glomerulus are particularly vulnerable to cellular defects resulting from altered tRNA modifications.

Whole exome sequencing frequently detects a monogenic cause in early onset nephrolithiasis and nephrocalcinosis. - Daga, Ankana; Majmundar, Amar J; Braun, Daniela A; Gee, Heon Yung; Lawson, Jennifer A; Shril, Shirlee; Jobst-Schwan, Tilman; Vivante, Asaf; Schapiro, David; Tan, Weizhen; Warejko, Jillian K; Widmeier, Eugen; et al. (Kidney Int, 2018)
The incidence of nephrolithiasis continues to rise. Previously, we showed that a monogenic cause could be detected in 11.4% of individuals with adult-onset nephrolithiasis or nephrocalcinosis and in 16.7-20.8% of individuals with onset before 18 years of age, using gene panel sequencing of 30 genes known to cause nephrolithiasis/nephrocalcinosis. To overcome the limitations of panel sequencing, we utilized whole exome sequencing in 51 families, who presented before age 25 years with at least one renal stone or with a renal ultrasound finding of nephrocalcinosis to identify the underlying molecular genetic cause of disease. In 15 of 51 families, we detected a monogenic causative mutation by whole exome sequencing. A mutation in seven recessive genes (AGXT, ATP6V1B1, CLDN16, CLDN19, GRHPR, SLC3A1, SLC12A1), in one dominant gene (SLC9A3R1), and in one gene (SLC34A1) with both recessive and dominant inheritance was detected. Seven of the 19 different mutations were not previously described as disease-causing. In one family, a causative mutation in one of 117 genes that may represent phenocopies of nephrolithiasis-causing genes was detected. In nine of 15 families, the genetic diagnosis may have specific implications for stone management and prevention. Several factors that correlated with the higher detection rate in our cohort were younger age at onset of nephrolithiasis/nephrocalcinosis, presence of multiple affected members in a family, and presence of consanguinity. Thus, we established whole exome sequencing as an efficient approach toward a molecular genetic diagnosis in individuals with nephrolithiasis/nephrocalcinosis who manifest before age 25 years.
Keywords: Adolescent; Age of Onset; Child; Child, Preschool; Disease Progression; Female; Genetic Association Studies; Genetic Markers; Genetic Predisposition to Disease; Heredity; Humans; Infant; Male; Mutation; Nephrocalcinosis; Nephrolithiasis; Pedigree; Phenotype; Predictive Value of Tests; Prognosis; Risk Factors; Tomography, X-Ray Computed; Ultrasonography; Whole Exome Sequencing; Young Adult

Whole Exome Sequencing of Patients with Steroid-Resistant Nephrotic Syndrome. - Warejko, Jillian K; Tan, Weizhen; Daga, Ankana; Schapiro, David; Lawson, Jennifer A; Shril, Shirlee; Lovric, Svjetlana; Ashraf, Shazia; Rao, Jia; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; et al. (Clin J Am Soc Nephrol, 2018)
BACKGROUND AND OBJECTIVES: Steroid-resistant nephrotic syndrome overwhelmingly progresses to ESRD. More than 30 monogenic genes have been identified to cause steroid-resistant nephrotic syndrome. We previously detected causative mutations using targeted panel sequencing in 30% of patients with steroid-resistant nephrotic syndrome. Panel sequencing has a number of limitations when compared with whole exome sequencing. We employed whole exome sequencing to detect monogenic causes of steroid-resistant nephrotic syndrome in an international cohort of 300 families. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Three hundred thirty-five individuals with steroid-resistant nephrotic syndrome from 300 families were recruited from April of 1998 to June of 2016. Age of onset was restricted to <25 years of age. Exome data were evaluated for 33 known monogenic steroid-resistant nephrotic syndrome genes. RESULTS: In 74 of 300 families (25%), we identified a causative mutation in one of 20 genes known to cause steroid-resistant nephrotic syndrome. In 11 families (3.7%), we detected a mutation in a gene that causes a phenocopy of steroid-resistant nephrotic syndrome. This is consistent with our previously published identification of mutations using a panel approach. We detected a causative mutation in a known steroid-resistant nephrotic syndrome gene in 38% of consanguineous families and in 13% of nonconsanguineous families, and 48% of children with congenital nephrotic syndrome. A total of 68 different mutations were detected in 20 of 33 steroid-resistant nephrotic syndrome genes. Fifteen of these mutations were novel. , , , and were the most common genes in which we detected a mutation. In another 28% of families, we detected mutations in one or more candidate genes for steroid-resistant nephrotic syndrome. CONCLUSIONS: Whole exome sequencing is a sensitive approach toward diagnosis of monogenic causes of steroid-resistant nephrotic syndrome. A molecular genetic diagnosis of steroid-resistant nephrotic syndrome may have important consequences for the management of treatment and kidney transplantation in steroid-resistant nephrotic syndrome.

Whole Exome Sequencing Reveals a Monogenic Cause of Disease in ≈43% of 35 Families With Midaortic Syndrome. - Warejko, Jillian K; Schueler, Markus; Vivante, Asaf; Tan, Weizhen; Daga, Ankana; Lawson, Jennifer A; Braun, Daniela A; Shril, Shirlee; Amann, Kassaundra; Somers, Michael J G; Rodig, Nancy M; Baum, Michelle A; et al. (Hypertension, 2018)
Midaortic syndrome (MAS) is a rare cause of severe childhood hypertension characterized by narrowing of the abdominal aorta in children and is associated with extensive vascular disease. It may occur as part of a genetic syndrome, such as neurofibromatosis, or as consequence of a pathological inflammatory disease. However, most cases are considered idiopathic. We hypothesized that in a high percentage of these patients, a monogenic cause of disease may be detected by evaluating whole exome sequencing data for mutations in 1 of 38 candidate genes previously described to cause vasculopathy. We studied a cohort of 36 individuals from 35 different families with MAS by exome sequencing. In 15 of 35 families (42.9%), we detected likely causal dominant mutations. In 15 of 35 (42.9%) families with MAS, whole exome sequencing revealed a mutation in one of the genes previously associated with vascular disease (, , , , and ). Ten of the 15 mutations have not previously been reported. This is the first report of , , or mutations in individuals with MAS. Mutations were detected in (6/15 families), (4/15 families), (3/15 families), and one family each for and Eight individuals had syndromic disease and 7 individuals had isolated MAS. Whole exome sequencing can provide conclusive molecular genetic diagnosis in a high fraction of individuals with syndromic or isolated MAS. Establishing an etiologic diagnosis may reveal genotype/phenotype correlations for MAS in the future and should, therefore, be performed routinely in MAS.
Keywords: Adolescent; Aorta, Abdominal; Aortic Valve Stenosis; Child; Child, Preschool; Cohort Studies; Female; Genetic Association Studies; Humans; Hypertension; Jagged-1 Protein; Male; Mutation; Neurofibromatoses; Neurofibromin 1; Pedigree; Syndrome; United States; Whole Exome Sequencing

Whole-Exome Sequencing Identifies Causative Mutations in Families with Congenital Anomalies of the Kidney and Urinary Tract. - van der Ven, Amelie T; Connaughton, Dervla M; Ityel, Hadas; Mann, Nina; Nakayama, Makiko; Chen, Jing; Vivante, Asaf; Hwang, Daw-Yang; Schulz, Julian; Braun, Daniela A; Schmidt, Johanna Magdalena; Schapiro, David; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Congenital anomalies of the kidney and urinary tract (CAKUT) are the most prevalent cause of kidney disease in the first three decades of life. Previous gene panel studies showed monogenic causation in up to 12% of patients with CAKUT. METHODS: We applied whole-exome sequencing to analyze the genotypes of individuals from 232 families with CAKUT, evaluating for mutations in single genes known to cause human CAKUT and genes known to cause CAKUT in mice. In consanguineous or multiplex families, we additionally performed a search for novel monogenic causes of CAKUT. RESULTS: In 29 families (13%), we detected a causative mutation in a known gene for isolated or syndromic CAKUT that sufficiently explained the patient's CAKUT phenotype. In three families (1%), we detected a mutation in a gene reported to cause a phenocopy of CAKUT. In 15 of 155 families with isolated CAKUT, we detected deleterious mutations in syndromic CAKUT genes. Our additional search for novel monogenic causes of CAKUT in consanguineous and multiplex families revealed a potential single, novel monogenic CAKUT gene in 19 of 232 families (8%). CONCLUSIONS: We identified monogenic mutations in a known human CAKUT gene or CAKUT phenocopy gene as the cause of disease in 14% of the CAKUT families in this study. Whole-exome sequencing provides an etiologic diagnosis in a high fraction of patients with CAKUT and will provide a new basis for the mechanistic understanding of CAKUT.

Advillin acts upstream of phospholipase C ϵ1 in steroid-resistant nephrotic syndrome. - Rao, Jia; Ashraf, Shazia; Tan, Weizhen; van der Ven, Amelie T; Gee, Heon Yung; Braun, Daniela A; Fehér, Krisztina; George, Sudeep P; Esmaeilniakooshkghazi, Amin; Choi, Won-Il; Jobst-Schwan, Tilman; Schneider, Ronen; et al. (J Clin Invest, 2017)
Steroid-resistant nephrotic syndrome (SRNS) is a frequent cause of chronic kidney disease. Here, we identified recessive mutations in the gene encoding the actin-binding protein advillin (AVIL) in 3 unrelated families with SRNS. While all AVIL mutations resulted in a marked loss of its actin-bundling ability, truncation of AVIL also disrupted colocalization with F-actin, thereby leading to impaired actin binding and severing. Additionally, AVIL colocalized and interacted with the phospholipase enzyme PLCE1 and with the ARP2/3 actin-modulating complex. Knockdown of AVIL in human podocytes reduced actin stress fibers at the cell periphery, prevented recruitment of PLCE1 to the ARP3-rich lamellipodia, blocked EGF-induced generation of diacylglycerol (DAG) by PLCE1, and attenuated the podocyte migration rate (PMR). These effects were reversed by overexpression of WT AVIL but not by overexpression of any of the 3 patient-derived AVIL mutants. The PMR was increased by overexpression of WT Avil or PLCE1, or by EGF stimulation; however, this increased PMR was ameliorated by inhibition of the ARP2/3 complex, indicating that ARP-dependent lamellipodia formation occurs downstream of AVIL and PLCE1 function. Together, these results delineate a comprehensive pathogenic axis of SRNS that integrates loss of AVIL function with alterations in the action of PLCE1, an established SRNS protein.
Keywords: Actin-Related Protein 2-3 Complex; Cell Movement; Diglycerides; Female; Humans; Male; Microfilament Proteins; Mutation; Nephrotic Syndrome; Phosphoinositide Phospholipase C; Podocytes; Pseudopodia

A Dominant Mutation in Nuclear Receptor Interacting Protein 1 Causes Urinary Tract Malformations Dysregulation of Retinoic Acid Signaling. - Vivante, Asaf; Mann, Nina; Yonath, Hagith; Weiss, Anna-Carina; Getwan, Maike; Kaminski, Michael M; Bohnenpoll, Tobias; Teyssier, Catherine; Chen, Jing; Shril, Shirlee; van der Ven, Amelie T; Ityel, Hadas; et al. (J Am Soc Nephrol, 2017)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of CKD in the first three decades of life. However, for most patients with CAKUT, the causative mutation remains unknown. We identified a kindred with an autosomal dominant form of CAKUT. By whole-exome sequencing, we identified a heterozygous truncating mutation (c.279delG, p.Trp93fs*) of the nuclear receptor interacting protein 1 gene () in all seven affected members. encodes a nuclear receptor transcriptional cofactor that directly interacts with the retinoic acid receptors (RARs) to modulate retinoic acid transcriptional activity. Unlike wild-type NRIP1, the altered NRIP1 protein did not translocate to the nucleus, did not interact with RAR, and failed to inhibit retinoic acid-dependent transcriptional activity upon expression in HEK293 cells. Notably, we also showed that treatment with retinoic acid enhanced NRIP1 binding to RAR RNA hybridization confirmed expression in the developing urogenital system of the mouse. In explant cultures of embryonic kidney rudiments, retinoic acid stimulated expression, whereas a pan-RAR antagonist strongly reduced it. Furthermore, mice heterozygous for a null allele of showed a CAKUT-spectrum phenotype. Finally, expression and knockdown experiments in confirmed an evolutionarily conserved role for in renal development. These data indicate that dominant mutations can cause CAKUT by interference with retinoic acid transcriptional signaling, shedding light on the well documented association between abnormal vitamin A levels and renal malformations in humans, and suggest a possible gene-environment pathomechanism in this disease.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Mice; Mutation; Nuclear Proteins; Nuclear Receptor Interacting Protein 1; Signal Transduction; Tretinoin; Urinary Tract

Exome sequencing in Jewish and Arab patients with rhabdomyolysis reveals single-gene etiology in 43% of cases. - Vivante, Asaf; Ityel, Hadas; Pode-Shakked, Ben; Chen, Jing; Shril, Shirlee; van der Ven, Amelie T; Mann, Nina; Schmidt, Johanna Magdalena; Segel, Reeval; Aran, Adi; Zeharia, Avraham; Staretz-Chacham, Orna; et al. (Pediatr Nephrol, 2017)
BACKGROUND: Rhabdomyolysis is a clinical emergency that may cause acute kidney injury (AKI). It can be acquired or due to monogenic mutations. Around 60 different rare monogenic forms of rhabdomyolysis have been reported to date. In the clinical setting, identifying the underlying molecular diagnosis is challenging due to nonspecific presentation, the high number of causative genes, and current lack of data on the prevalence of monogenic forms. METHODS: We employed whole exome sequencing (WES) to reveal the percentage of rhabdomyolysis cases explained by single-gene (monogenic) mutations in one of 58 candidate genes. We investigated a cohort of 21 unrelated families with rhabdomyolysis, in whom no underlying etiology had been previously established. RESULTS: Using WES, we identified causative mutations in candidate genes in nine of the 21 families (43%). We detected disease-causing mutations in eight of 58 candidate genes, grouped into the following categories: (1) disorders of fatty acid metabolism (CPT2), (2) disorders of glycogen metabolism (PFKM and PGAM2), (3) disorders of abnormal skeletal muscle relaxation and contraction (CACNA1S, MYH3, RYR1 and SCN4A), and (4) disorders of purine metabolism (AHCY). CONCLUSIONS: Our findings demonstrate a very high detection rate for monogenic etiologies using WES and reveal broad genetic heterogeneity for rhabdomyolysis. These results highlight the importance of molecular genetic diagnostics for establishing an etiologic diagnosis. Because these patients are at risk for recurrent episodes of rhabdomyolysis and subsequent risk for AKI, WES allows adequate prophylaxis and treatment for these patients and their family members and enables a personalized medicine approach.
Keywords: Adolescent; Adult; Arabs; Child; Exome; Genetic Predisposition to Disease; Humans; Jews; Mutation; Rhabdomyolysis; Whole Exome Sequencing

Exome-wide Association Study Identifies GREB1L Mutations in Congenital Kidney Malformations. - Sanna-Cherchi, Simone; Khan, Kamal; Westland, Rik; Krithivasan, Priya; Fievet, Lorraine; Rasouly, Hila Milo; Ionita-Laza, Iuliana; Capone, Valentina P; Fasel, David A; Kiryluk, Krzysztof; Kamalakaran, Sitharthan; Bodria, Monica; et al. (Am J Hum Genet, 2017)
Renal agenesis and hypodysplasia (RHD) are major causes of pediatric chronic kidney disease and are highly genetically heterogeneous. We conducted whole-exome sequencing in 202 case subjects with RHD and identified diagnostic mutations in genes known to be associated with RHD in 7/202 case subjects. In an additional affected individual with RHD and a congenital heart defect, we found a homozygous loss-of-function (LOF) variant in SLIT3, recapitulating phenotypes reported with Slit3 inactivation in the mouse. To identify genes associated with RHD, we performed an exome-wide association study with 195 unresolved case subjects and 6,905 control subjects. The top signal resided in GREB1L, a gene implicated previously in Hoxb1 and Shha signaling in zebrafish. The significance of the association, which was p = 2.0 × 10 for novel LOF, increased to p = 4.1 × 10 for LOF and deleterious missense variants combined, and augmented further after accounting for segregation and de novo inheritance of rare variants (joint p = 2.3 × 10). Finally, CRISPR/Cas9 disruption or knockdown of greb1l in zebrafish caused specific pronephric defects, which were rescued by wild-type human GREB1L mRNA, but not mRNA containing alleles identified in case subjects. Together, our study provides insight into the genetic landscape of kidney malformations in humans, presents multiple candidates, and identifies SLIT3 and GREB1L as genes implicated in the pathogenesis of RHD.
Keywords: Alleles; Animals; Case-Control Studies; Clustered Regularly Interspaced Short Palindromic Repeats; Congenital Abnormalities; Exome; Female; Genetic Heterogeneity; Genome-Wide Association Study; Genotype; Heredity; Homozygote; Humans; Kidney; Kidney Diseases; Male; Membrane Proteins; Mice; Mutation; Neoplasm Proteins; Phenotype; RNA, Long Noncoding; Urinary Tract; Urogenital Abnormalities; Zebrafish

Mutations in KEOPS-complex genes cause nephrotic syndrome with primary microcephaly. - Braun, Daniela A; Rao, Jia; Mollet, Geraldine; Schapiro, David; Daugeron, Marie-Claire; Tan, Weizhen; Gribouval, Olivier; Boyer, Olivia; Revy, Patrick; Jobst-Schwan, Tilman; Schmidt, Johanna Magdalena; Lawson, Jennifer A; et al. (Nat Genet, 2017)
Galloway-Mowat syndrome (GAMOS) is an autosomal-recessive disease characterized by the combination of early-onset nephrotic syndrome (SRNS) and microcephaly with brain anomalies. Here we identified recessive mutations in OSGEP, TP53RK, TPRKB, and LAGE3, genes encoding the four subunits of the KEOPS complex, in 37 individuals from 32 families with GAMOS. CRISPR-Cas9 knockout in zebrafish and mice recapitulated the human phenotype of primary microcephaly and resulted in early lethality. Knockdown of OSGEP, TP53RK, or TPRKB inhibited cell proliferation, which human mutations did not rescue. Furthermore, knockdown of these genes impaired protein translation, caused endoplasmic reticulum stress, activated DNA-damage-response signaling, and ultimately induced apoptosis. Knockdown of OSGEP or TP53RK induced defects in the actin cytoskeleton and decreased the migration rate of human podocytes, an established intermediate phenotype of SRNS. We thus identified four new monogenic causes of GAMOS, describe a link between KEOPS function and human disease, and delineate potential pathogenic mechanisms.
Keywords: Animals; Apoptosis; Carrier Proteins; Cell Movement; CRISPR-Cas Systems; Cytoskeleton; DNA Repair; Endoplasmic Reticulum Stress; Gene Knockout Techniques; Hernia, Hiatal; Humans; Intracellular Signaling Peptides and Proteins; Metalloendopeptidases; Mice; Microcephaly; Models, Molecular; Multiprotein Complexes; Mutation; Nephrosis; Nephrotic Syndrome; Podocytes; Protein Conformation; Protein-Serine-Threonine Kinases; RNA Processing, Post-Transcriptional; RNA, Transfer; Telomere Homeostasis; Zebrafish; Zebrafish Proteins

Mutations in sphingosine-1-phosphate lyase cause nephrosis with ichthyosis and adrenal insufficiency. - Lovric, Svjetlana; Goncalves, Sara; Gee, Heon Yung; Oskouian, Babak; Srinivas, Honnappa; Choi, Won-Il; Shril, Shirlee; Ashraf, Shazia; Tan, Weizhen; Rao, Jia; Airik, Merlin; Schapiro, David; et al. (J Clin Invest, 2017)
Steroid-resistant nephrotic syndrome (SRNS) causes 15% of chronic kidney disease cases. A mutation in 1 of over 40 monogenic genes can be detected in approximately 30% of individuals with SRNS whose symptoms manifest before 25 years of age. However, in many patients, the genetic etiology remains unknown. Here, we have performed whole exome sequencing to identify recessive causes of SRNS. In 7 families with SRNS and facultative ichthyosis, adrenal insufficiency, immunodeficiency, and neurological defects, we identified 9 different recessive mutations in SGPL1, which encodes sphingosine-1-phosphate (S1P) lyase. All mutations resulted in reduced or absent SGPL1 protein and/or enzyme activity. Overexpression of cDNA representing SGPL1 mutations resulted in subcellular mislocalization of SGPL1. Furthermore, expression of WT human SGPL1 rescued growth of SGPL1-deficient dpl1Δ yeast strains, whereas expression of disease-associated variants did not. Immunofluorescence revealed SGPL1 expression in mouse podocytes and mesangial cells. Knockdown of Sgpl1 in rat mesangial cells inhibited cell migration, which was partially rescued by VPC23109, an S1P receptor antagonist. In Drosophila, Sply mutants, which lack SGPL1, displayed a phenotype reminiscent of nephrotic syndrome in nephrocytes. WT Sply, but not the disease-associated variants, rescued this phenotype. Together, these results indicate that SGPL1 mutations cause a syndromic form of SRNS.
Keywords: Aldehyde-Lyases; Animals; Cell Line; Cell Movement; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Ichthyosis, Lamellar; Male; Mesangial Cells; Mice; Mice, Knockout; Mutation; Nephrotic Syndrome; Protein Transport; Rats

Whole-Exome Sequencing Reveals Mutations in a Clinically Unrecognizable Patient with Syndromic CAKUT: A Case Report. - van der Ven, Amelie T; Shril, Shirlee; Ityel, Hadas; Vivante, Asaf; Chen, Jing; Hwang, Daw-Yang; Laricchia, Kristen M; Lek, Monkol; Tasic, Velibor; Hildebrandt, Friedhelm (Mol Syndromol, 2017)
We present the case of a patient of Macedonian origin with unilateral renal agenesis and ureterovesical junction obstruction in combination with further abnormalities including midface hypoplasia, scoliosis as well as camptodactyly of one toe. Whole-exome sequencing analysis revealed compound heterozygous variants in the gene. Recessive variants in are a known cause of van Maldergem syndrome (VMS) in which congenital anomalies of the kidney and urinary tract are a less characteristic but common feature. The initial presentation of our patient was not clinically recognizable. However, in view of the molecular findings, the most likely diagnosis is a mild manifestation of VMS. Only very few publications have reported patients with VMS and mutations in to date. With this case, we hope to provide further insight into the phenotypic variability of this syndrome.

Mutations in nuclear pore genes NUP93, NUP205 and XPO5 cause steroid-resistant nephrotic syndrome. - Braun, Daniela A; Sadowski, Carolin E; Kohl, Stefan; Lovric, Svjetlana; Astrinidis, Susanne A; Pabst, Werner L; Gee, Heon Yung; Ashraf, Shazia; Lawson, Jennifer A; Shril, Shirlee; Airik, Merlin; Tan, Weizhen; et al. (Nat Genet, 2016)
Nucleoporins are essential components of the nuclear pore complex (NPC). Only a few diseases have been attributed to NPC dysfunction. Steroid-resistant nephrotic syndrome (SRNS), a frequent cause of chronic kidney disease, is caused by dysfunction of glomerular podocytes. Here we identify in eight families with SRNS mutations in NUP93, its interaction partner NUP205 or XPO5 (encoding exportin 5) as hitherto unrecognized monogenic causes of SRNS. NUP93 mutations caused disrupted NPC assembly. NUP93 knockdown reduced the presence of NUP205 in the NPC, and, reciprocally, a NUP205 alteration abrogated NUP93 interaction. We demonstrate that NUP93 and exportin 5 interact with the signaling protein SMAD4 and that NUP93 mutations abrogated interaction with SMAD4. Notably, NUP93 mutations interfered with BMP7-induced SMAD transcriptional reporter activity. We hereby demonstrate that mutations of NUP genes cause a distinct renal disease and identify aberrant SMAD signaling as a new disease mechanism of SRNS, opening a potential new avenue for treatment.
Keywords: Age of Onset; Amino Acid Sequence; Animals; Cell Movement; Cell Proliferation; Cells, Cultured; Child; Child, Preschool; Drug Resistance; Female; Genes, Recessive; Genetic Association Studies; Genetic Linkage; HEK293 Cells; Humans; Infant; Karyopherins; Male; Mice; Molecular Sequence Data; Mutation; Nephrotic Syndrome; Nuclear Pore Complex Proteins; Oxidative Stress; Podocytes; Sequence Analysis, DNA; Steroids; Xenopus laevis

Whole exome sequencing identifies causative mutations in the majority of consanguineous or familial cases with childhood-onset increased renal echogenicity. - Braun, Daniela A; Schueler, Markus; Halbritter, Jan; Gee, Heon Yung; Porath, Jonathan D; Lawson, Jennifer A; Airik, Rannar; Shril, Shirlee; Allen, Susan J; Stein, Deborah; Al Kindy, Adila; Beck, Bodo B; et al. (Kidney Int, 2016)
Chronically increased echogenicity on renal ultrasound is a sensitive early finding of chronic kidney disease that can be detected before manifestation of other symptoms. Increased echogenicity, however, is not specific for a certain etiology of chronic kidney disease. Here, we performed whole exome sequencing in 79 consanguineous or familial cases of suspected nephronophthisis in order to determine the underlying molecular disease cause. In 50 cases, there was a causative mutation in a known monogenic disease gene. In 32 of these cases whole exome sequencing confirmed the diagnosis of a nephronophthisis-related ciliopathy. In 8 cases it revealed the diagnosis of a renal tubulopathy. The remaining 10 cases were identified as Alport syndrome (4), autosomal-recessive polycystic kidney disease (2), congenital anomalies of the kidney and urinary tract (3), and APECED syndrome (1). In 5 families, in whom mutations in known monogenic genes were excluded, we applied homozygosity mapping for variant filtering and identified 5 novel candidate genes (RBM48, FAM186B, PIAS1, INCENP, and RCOR1) for renal ciliopathies. Thus, whole exome sequencing allows the detection of the causative mutation in 2/3 of affected individuals, thereby presenting the etiologic diagnosis, and allows identification of novel candidate genes.
Keywords: Age of Onset; Cohort Studies; DNA Mutational Analysis; Exome; Humans; Kidney Diseases, Cystic; Renal Insufficiency, Chronic

Mutations in TBX18 Cause Dominant Urinary Tract Malformations via Transcriptional Dysregulation of Ureter Development. - Vivante, Asaf; Kleppa, Marc-Jens; Schulz, Julian; Kohl, Stefan; Sharma, Amita; Chen, Jing; Shril, Shirlee; Hwang, Daw-Yang; Weiss, Anna-Carina; Kaminski, Michael M; Shukrun, Rachel; Kemper, Markus J; et al. (Am J Hum Genet, 2015)
Congenital anomalies of the kidneys and urinary tract (CAKUT) are the most common cause of chronic kidney disease in the first three decades of life. Identification of single-gene mutations that cause CAKUT permits the first insights into related disease mechanisms. However, for most cases the underlying defect remains elusive. We identified a kindred with an autosomal-dominant form of CAKUT with predominant ureteropelvic junction obstruction. By whole exome sequencing, we identified a heterozygous truncating mutation (c.1010delG) of T-Box transcription factor 18 (TBX18) in seven affected members of the large kindred. A screen of additional families with CAKUT identified three families harboring two heterozygous TBX18 mutations (c.1570C>T and c.487A>G). TBX18 is essential for developmental specification of the ureteric mesenchyme and ureteric smooth muscle cells. We found that all three TBX18 altered proteins still dimerized with the wild-type protein but had prolonged protein half life and exhibited reduced transcriptional repression activity compared to wild-type TBX18. The p.Lys163Glu substitution altered an amino acid residue critical for TBX18-DNA interaction, resulting in impaired TBX18-DNA binding. These data indicate that dominant-negative TBX18 mutations cause human CAKUT by interference with TBX18 transcriptional repression, thus implicating ureter smooth muscle cell development in the pathogenesis of human CAKUT.
Keywords: Base Sequence; Electrophoretic Mobility Shift Assay; Exome; Gene Expression Regulation, Developmental; Genes, Dominant; HEK293 Cells; Humans; Immunohistochemistry; Immunoprecipitation; Microscopy, Fluorescence; Molecular Sequence Data; Muscle, Smooth; Mutation; Pedigree; Sequence Analysis, DNA; T-Box Domain Proteins; Ureter; Urinary Tract